Eye-tracking contribution on processing of (implicit) reading comprehension - Cristina de- (Springer, 2024)
Abstract Reading comprehension is a fundamental skill to be developed from the early stages of reading acquisition and it is essential for both formative and personal learning. This study examines eye-tracking as a useful and complementary tool in the assessment and improvement of implicit reading comprehension. The aim is to understand the role of eye-tracking in implicit reading comprehension and, complementarily, in intervening skills such as vocabulary, rapid automatized naming, and processing speed. In a final sample of 7-8 year-old 67 students, tests for implicit reading comprehension (literal, inferential, and total), eye-tracking measures, vocabulary, rapid automatized naming, processing speed, as well as tests to control for intellectual and attentional levels were administered. The results of the correlational and regression analyses indicate the existence of predictive relationships between (i) implicit reading comprehension and eye-tracking measures, and additionally, (ii) between intervening skills (vocabulary, rapid automatized naming, processing speed) and eye-tracking measures, and (iii) between implicit reading comprehension and intervening skills (vocabulary, rapid automatized naming, processing speed). In summary, better performance in implicit reading comprehension (literal, inferential, and total) is related to and explained by shorter eye movement times in recognition and access to meaning, larger vocabulary, and faster rapid automatized naming and processing speed. Furthermore, eye-tracking measures are better predictors of implicit reading comprehension. These findings provide promising evidence for the contribution of eye-tracking to optimising the level of implicit reading comprehension, which is applied daily in classrooms.